Short value horticulture chains in Lima- Perú - Rendón Schneir, Eric (2021)
Lima is the capital and the largest city of Peru with 10 million inhabitants and the COVID-19 pandemic has exposed vulnerabilities related to food security. Although agricultural areas have decreased in the last 45 years, certain horticulture consumption proceeds still from parcels situated in the peripheric area of the city. It was used the Self-Sufficiency Ratio (SSR) for   horticulture crops in Lima city, in order to evaluate the performance of this index between 2012 and 2019; additionally it was used a correlation for evaluating the relationship between per-capita incomes and horticulture consumption per-capita. The objective of this research is to analyze horticulture production in Lima in order to generate information for providing to policy makers and researchers, criteria for the development of urban agriculture in Lima city and this research seeks to contribute for improving food security and nutrition in the Lima city, and also for generating environmental and social improvements.